Students’ Responses through the Use of Edpuzzle as an Application in Achieving Listening Comprehension - Rahmita Egilistiani; Ratu Prayuana (Linguists : Journal Of Linguistics and Language Teaching, 2021)
This study aims to find out students’ responses through the use of Edpuzzleas an application in achieving listening comprehension. As a foreign language in Indonesia, sometimes students will face some obstacles and difficulties in learning the English language; the obstacles that must be faced by the first-year students, where else there are some skills to learn at the same time which will worsen their learning process as it will be hard to be understood with low competence in the first place. The use of Edpuzzle here is expected to help to get through the initial problem related to the achievement of listening comprehension. Edpuzzle is a platform that helps teachers invite students to have fun learning using videos. These videos can be edited and adjusted to the goal of the teachers in the class activity on a particular subject; they can be cut, recorded new voice, and add some more questions if it is needed. In this study, the participants are first-year students in English Literature of the University of Pamulang (UNPAM) with 54 students in the subject of listening. The data were collected by using a questionnaire and the discussion in the e-learning forum of UNPAM in listening subjects. The results of the study revealed that the students were interested in learning the English language of the subject listening using Edpuzzle as it lifts their consciousness so that they can overwhelmingly enjoy the process of learning. They also found out that the subject listening is becoming entertaining to learn and can be a fun learning too even with the task that is difficult for them, alongside their thought that learning English using Edpuzzle can help them improve their listening comprehension in a fun way possible.